Islam, Muslims and 2020 #EndSARS Protests in Nigeria - Khalidu Adewale Afolabi (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2023)
The 2020 #EndSARS is a youth-enthusiastic social movement in Nigeria against brutality and inhuman excesses of the Special Anti-Robbery Squad unit of the Nigerian Police Force. The protest movement started on social media and transmited to spatio-temporal platforms as numerous Nigerian youths were scattered on major streets and landmarks of the country to express their dissatisfaction with the operations and methods of the Special Anti-Robbery Squad (SARS). The protest was held by youths across different tribes, races and religions (with Muslims inclusive.) Just as the movement continued to increase, the participation of Nigerian Muslim youths in the protest became entwined in controversies as young Nigerian Muslim intellectuals debated the permissibility and impermissibility of protest for an ideal Muslim regardless of the circumstances. Numerous studies have examined protests, rebellions, uprisings, and coup d’états amongst other political issues affecting democracy, but they hardly study protests in the light of Islam and Muslims. This paper therefore seeks to explore this gap with a qualitative research by revisiting the history of Islamic civilization in the first few decades of Islam, approaching some Sharī‘ah principles and rereading the sensitive Islamic texts on obedience to authority in the context of contemporary realities surrounding the Nigerian Muslim ’Ummah. The paper concludes that while a protest is typically detestable under Islamic polity, it may rob Islam of its essence if such an opinion is upheld for Nigerian Muslims on 2020 #EndSARS, without considering the social, political, and constitutional factors influencing the movement in Nigeria.